Legal regulation of migration for family reunification (Journal of actual problems of jurisprudence, 2018)
This article discusses the legal regulation of immigration for family reunification. We consider immigrationlegislation of the Republic of Kazakhstan. The analysis of foreign experience in managing migration forfamily reunification. Particular attention is paid to the definition of the family as the foundation of modernsociety and one of the basic human rights.Keywords: migration, family reunification, immigration, emigration, family, immigration law, human rights.